A computational stylometric analysis of characterization by playwrights - Lynch, Gerard (Trinity College Dublin. Long Room Hub, 2008)
Is it possible for an author to create characters truly independent of their own voice? Do characters from the same play exhibit similar characteristics in style? Are some playwrights arguably better at creating unique characters that transcend their own personal style and become individual entities in their own right? Are playwrights who adhere to iambic pentameter or other metrical constraint thereby confined to the construction of characters whose language cannot be differentiated on the basis of the syntax of their language? This study seeks to address these questions and provide more information about what constitutes characterization in plays. Methods from the field of authorship attribution, which are normally used to determine the provenance of anonymous texts are used on the individual text of characters from a number of playwrights.
Exhibited at the Glucksman Memorial Symposium on June 12th 2008
Keywords: Computational stylometric analysis; Characterisation -- dramatic; Authorship attribution -- methodology of; William Shakespeare